THE INFLUENCE OF A LULLABY SONG ON A CHILD'S CONSCIOUSNESS AND CONSCIOUSNESS. ONEIRIC AND APOTROPEIC FUNCTIONS - Марчун, Оксана (SWorldJournal, 2023)
The article presents the results of a study of the texts of lullabies, which have a special effect on the child's consciousness and subconsciousness. A lullaby is a genre of folk family lyrics, rich in imagery and a variety of motives, which is clearly a